Bone substitutes for peri-implant defects of postextraction implants - Santos, Pâmela Letícia; Gulinelli, Jéssica Lemos; Telles, Cristino da Silva; Betoni Júnior, Walter; Okamoto, Roberta [UNESP]; Chiacchio Buchignani, Vivian; Queiroz, Thallita Pereira (Hindawi, 2013)
Placement of implants in fresh sockets is an alternative to try to reduce physiological resorption of alveolar ridge after tooth extraction. This surgery can be used to preserve the bone architecture and also accelerate the restorative procedure. However, the diastasis observed between bone and implant may influence osseointegration. So, autogenous bone graft and/or biomaterials have been used to fill this gap. Considering the importance of bone repair for treatment with implants placed immediately after tooth extraction, this study aimed to present a literature review about biomaterials surrounding immediate dental implants. The search included 56 articles published from 1969 to 2012. The results were based on data analysis and discussion. It was observed that implant fixation immediately after extraction is a reliable alternative to reduce the treatment length of prosthetic restoration. In general, the biomaterial should be used to increase bone/implant contact and enhance osseointegration.